2012
DOI: 10.1007/s11832-012-0386-2
|View full text |Cite
|
Sign up to set email alerts
|

Femoro-acetabular impingement: The diagnosis—a review

Abstract: Background The recognition of the importance of femoral acetabular impingement (FAI) as a potential cause of hip pain has been stimulated by major efforts to salvage hip joints by reconstruction in order to prevent or delay the need for replacement. The purpose of this review is to define the nature of FAI, the various types, and how to make the diagnosis. Methods The review describes the characteristics of the hip that cause FAI and emphasizes understanding that the femoral and acetabular components normally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This sign indicates increased coverage, predisposing the patient to posterior impingement, which is less common. Protrusio acetabuli is noted when the medial margin of the femoral head is at or crosses the ilioischial line, and it represents anterior overcoverage of the femoral head (26). The lateral center edge angle (>39°) and Tönnis angle (<0°) also are used to estimate femoral head coverage at radiographic evaluation.…”
Section: Femoroacetabular Impingementmentioning
confidence: 99%
See 1 more Smart Citation
“…This sign indicates increased coverage, predisposing the patient to posterior impingement, which is less common. Protrusio acetabuli is noted when the medial margin of the femoral head is at or crosses the ilioischial line, and it represents anterior overcoverage of the femoral head (26). The lateral center edge angle (>39°) and Tönnis angle (<0°) also are used to estimate femoral head coverage at radiographic evaluation.…”
Section: Femoroacetabular Impingementmentioning
confidence: 99%
“…They also found that there is greater anteversion with further distance from the acetabular roof. Because of these differences, any report of the degree of version should include the level of the acetabulum from which the measurement was made (26).…”
Section: Femoroacetabular Impingementmentioning
confidence: 99%
“…59 Secondary cam FAI may follow slipped capital femoral epiphysis, Perthes disease, developmental hip dysplasia, protrusio acetabula, juvenile idiopathic arthritis, infection, trauma, or surgical interventions such as pelvic or acetabular osteotomies. 56,60 The radiographic and MRI signs that may indicate FAI are summarized in ►Table 5 [60][61][62] and illustrated in ►Figs. 10 to 13.…”
Section: Impingement Syndromesmentioning
confidence: 99%
“…Some authors proposed that growth disturbances affect not only the acetabulum but also the entire innominate bone [ 14 , 17 , 18 ]. To our knowledge, no one has focused on the influence of innominate bone position in one of the major conditions leading to osteoarthritis of the hip, femoroacetabular impingement, (FAI), in which the influence of the position of the entire pelvis on conflict of the femur and acetabulum has been reported several times [ 19 , 20 ]. There have also been no studies that assessed the influence of the innominate bone position on the acetabulum under physiologic conditions.…”
Section: Introductionmentioning
confidence: 99%